Hyponatraemia in patients with crush syndrome during the Wenchuan earthquake. Issue 9 (26th September 2012) - Zhang, Li; Fu, Ping; Wang, Li; Cai, Guangyan; Zhang, Lin; Chen, Dezheng; Guo, Dongyang; Sun, Xuefeng; Chen, Fuqiong; Bi, Weihong; Zeng, Xinjie; Li, Haiyan; et al.
Abstract : Background: Although sodium disturbances are common in hospitalised patients, no study has specifically investigated the epidemiology of hyponatraemia in patients with crush syndrome. Objectives: To describe the incidence of hyponatraemia and assess its effect on outcome in patients with crush syndrome during the Wenchuan earthquake. Methods: A retrospective study was conducted in 17 reference hospitals during the Wenchuan earthquake. We excluded patients younger than 15 years and those with missing sodium values within 3 days after being rescued from the ruins. Results: Hyponatraemia (serum sodium concentration <135 mmol/l) was seen in 91/180 (50.6%) patients on admission. Compared with patients with normonatraemia, those with hyponatraemia were younger, had more severe traumatic injury and renal failure, underwent more fasciotomies, received more blood transfusion and renal replacement therapy. In the multivariable-adjusted model, the number of extremity injuries (OR=1.59, 95% CI 1.08 to 2.33) and serum creatinine (OR=1.30, 95% CI 1.07 to 1.59) were independently associated with the occurrence of hyponatraemia. Covariate adjusted multiple logistic regression analysis showed an independent mortality risk rising with hyponatraemia (OR=5.74, 95% CI 1.18 to 28.00). Conclusions: Hyponatraemia was common in the patients with crush syndrome during the Wenchuan earthquake and associated with poor prognosis. Water, commercial drinks and hypotonic intravenous fluids should be supplied carefully to patients with crush syndrome.